2013
DOI: 10.1016/j.earscirev.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on climate oscillations: CMIP5 general circulation models versus a semi-empirical harmonic model based on astronomical cycles

Abstract: Power spectra of global surface temperature (GST) records (available since 1850) reveal major periodicities at about 9.1, 10-11, 19-22 and 59-62 years. Equivalent oscillations are found in numerous multisecular paleoclimatic records. The Coupled Model Intercomparison Project 5 (CMIP5) general circulation models (GCMs), to be used in the IPCC Fifth Assessment Report (AR5, 2013), are analyzed and found not able to reconstruct this variability. In particular, from 2000 to 2013.5 a GST plateau is observed while th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
191
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(205 citation statements)
references
References 141 publications
(284 reference statements)
12
191
0
2
Order By: Relevance
“…The Coupled Model Intercomparison Project Phase 5 (CMIP5) used to study climate change (Scafetta 2013c) currently recommends the use of a solar forcing function deduced from the TSI proxy model originally proposed by Lean and collaborators (Wang et al 2005;Kopp et al 2007). Lean's recent models show a relatively small secular trend (about 1 W/m 2 ) from the Maunder minimum (1645-1715) to the present with a peak about 1960 and it is quasi stationary since.…”
mentioning
confidence: 99%
“…The Coupled Model Intercomparison Project Phase 5 (CMIP5) used to study climate change (Scafetta 2013c) currently recommends the use of a solar forcing function deduced from the TSI proxy model originally proposed by Lean and collaborators (Wang et al 2005;Kopp et al 2007). Lean's recent models show a relatively small secular trend (about 1 W/m 2 ) from the Maunder minimum (1645-1715) to the present with a peak about 1960 and it is quasi stationary since.…”
mentioning
confidence: 99%
“…This natural climatic variability is confirmed by historical inferences [11] and by climate proxy reconstructions spanning the entire Holocene [12,13]. A millennial climatic oscillation would suggest that a significant percentage of the warming observed since 1850 could simply be a recovery from the Little Ice Age of the 14 th -18 th centuries and that throughout the 20 th century the climate naturally returned to a warm phase as it happened during the Roman and the Medieval warm periods [9,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 51%
“…Detailed data analysis [15,19] has concluded that the climatic effects of the radiative forcing is about half of that simulated by the CMIP5 GCMs. The climate sensitivity to CO2 doubling of the CMIP5 GCMs is about 3.…”
Section: Semi-empirical Model Predictionmentioning
confidence: 99%
See 2 more Smart Citations